The Efficacy of Inhaled Methoxyflurane Versus Intravenous Sedation for the Reduction of Acute Shoulder Dislocation - Iemsaengchairat, Chavalit (Journal of Southeast Asian Orthopaedics, 2024)
Purpose: Anterior shoulder dislocation is one of the most common emergency orthopedic conditions. In general practice, intravenous sedation is the standard treatment to relax patients during shoulder reduction procedures. Sedatives and analgesics are drugs that have side effects after administration, especially when administered intravenously. They can depress neurological function and cause respiratory and cardiovascular system side effects. Self-inhaled methoxyflurane relieves moderate to severe pain. Hospitals may benefit from minimized respiratory and cardiovascular side effects. Methods: This randomized controlled trial included 50 patients who were randomly assigned to two groups: the inhaled methoxyflurane group (Inh Group) and the intravenous sedation group (IV Group). All patients were assessed for efficacy, procedure duration, pain score during reduction, patient satisfaction, and adverse effects. Results: Fifty patients satisfied the inclusion requirement: 25 each in the Inh and IV Groups. Reduction was successfully achieved in 92% and 88% of the patients in the Inh and IV Group, respectively. The mean procedural time was 6.4 min and 15.4 min the Inh and IV Group, respectively. Moreover, the mean recovery time was 22.5 min in the Inh Group and 32.4 min in the IV Group. Conclusions: Inhaled methoxyflurane has better efficacy in reducing acute shoulder dislocation than intravenous sedation alone. Procedural and recovery times were shorter in the Inh Group. Adverse events (hemodynamic instability, desaturation, nausea, vomiting, drowsiness, and dizziness) were more frequent in the IV Group than in the Inh Group.